What lies ahead: Ten predictions for 2015. Issue 3 (December 2014) - Legrain, Philippe; Pettifor, Ann; Gardiner, Laura; Torrance, David; Jacques, Martin; Crabtree, James; Jacobs, Michael; Nave, Kathryn; Taylor, Matthew; Glaser, Eliane
<x xml:space="preserve">Abstract</x> 2014 ends in uncertainty, with economic stagnation, health crisis in west Africa, and war in the Ukraine and Middle East. Yet there is optimism, on climate change action, growth in Asia and Africa, and new technology. Juncture asked leading commentators to look ahead to 2015 on key issues facing Britain and the world.